A Critical Discourse Analysis of the Reconstructed National Identities in Selected Scottish and British Political Speeches with Reference to the Scottish Referendum - حسين ساره علي (lark, 2019)
Abstract This paper presents a critical discourse analysis of the discursive construction of national identity in selected political discourses. The nationalist narratives affect the ways people view problems that are related to them as a group, i.e. related to their ethnicity, nation, and country. Because of the effective role of the national narratives in directing people’s decisions, the study aims to investigate the ways in which national identities are maintained or reproduced in political discourse to reach political purposes. Thus, the researchers use a qualitative thematic analysis based on three levels to investigate the construction of the national identity in discourse. To achieve this aim, the study analyses two political speeches in which one of them is presented by the First Minister of Scotland Alex Salmond and the second one is given by the Prime Minister of the UK David Cameron. Both speeches are presented a day after the Scottish independence referendum. The researchers employ Wodak, de Cillia, Reisigl and Liebhart’s (2009) theory of the discursive construction of national identity to examine the strategies that are used by those opposing sides to maintain or reproduce a specific national identification. The study arrives at identifying certain strategies used to express the opposing views of both politicians to construct, maintain or destroy national identities.